Instrumental neutron activation analysis of Inka and local pottery from northern Chile's Atacama Desert. (October 2016) - Williams, Verónica I.; Santoro, Calogero M.; Speakman, Robert J.; Glascock, Michael D.; Romero Guevara, Álvaro Luis; Valenzuela, Daniela; Standen, Vivien G.; D'Altroy, Terence N.
Abstract: This paper presents the results of bulk chemical compositional analyses of ceramic pastes through Instrumental Neutron Activation Analysis (INAA), which is the most precise method available for this kind of research. The analyses were carried out on 94 fragments of pottery from several archaeological sites in northern Chile's Atacama Desert. We aimed to examine the possible origins of pottery vessels distinguished by Inka and local styles within the process of the Inka State expansion into the territories south of Cusco, known as Collasuyu. On the basis of these analyses, we discuss the idea that the State introduced to the zone pottery with Inka iconographic styles from the Lake Titicaca region (more than 500 km away). But, more important, the State seems to have encouraged the replication of State pottery standards by local artisans, who consciously or unconsciously maintained certain traditional procedures. This means that skilled local artisans imitated Inka iconographic style but using paste of local origin. These results show the importance of archaeometric analysis of high-prestige fine Inka and local pottery as it sheds light on how the State managed their political strategies, their impact on the prehistoric polities of northern Chile (NCh). Highlights: Inka pottery used in the expansion of the State was manufactured in different centers of production. In northern Chile three major pottery styles were consumed as symbol of power and prestige. INAA show that the State introduced vessels made in the Bolivia Altiplano. INAA show also that local artisans emulated the Inka paraphernalia with local raw materials. Interrelationship between State and local communities occurred with some cultural social independence.